Cognitive remediation for depression vulnerability: Current challenges and new directions - Vander Zwalmen, Yannick; Hoorelbeke, Kristof; Liebaert, Eveline; Nève de Mévergnies, Constance; Koster, Ernst H. (Frontiers in Psychology, 2022)
It is increasingly acknowledged that cognitive impairment can play an important role in depression vulnerability. Therefore, cognitive remediation strategies, and cognitive control training (CCT) procedures have gained attention in recent years as possible interventions for depression. Recent studies suggest a small to medium effect on indicators of depression vulnerability. Despite initial evidence for the efficacy and effectiveness of CCT, several central questions remain. In this paper we consider the key challenges for the clinical implementation of CCT, including exploration of (1) potential working mechanisms and related to this, moderators of training effects, (2) necessary conditions under which CCT could be optimally administered, such as dose requirements and training schedules and (3) how CCT could interact with or augment existing treatments of depression. Revisiting the cognitive control training literature, we also reflect upon the possibilities to evolve towards a stratified medicine approach, in which individual differences could be taken into account and used to optimize prevention of depression.